A new methodology using beam elements for the analysis of steel frames subjected to non-uniform temperatures due to fires. (June 2021) - Pallares-Muñoz, Myriam R.; Paya-Zaforteza, Ignacio; Hospitaler, Antonio
Abstract: Non-uniform heating in structures under fire involves the appearance of 3D-phenomena and typically requires the use of complex models built with finite elements shell or solid. Although different procedures have been developed to model the complex thermo-mechanical phenomenon, there is no simple, accurate, and low-cost computational methodology involving the space–time variation of the temperature and displacement fields that opens the path advancing more easily towards modeling more complex structural problems in a fire situation. To overcome this knowledge-gap, this paper presents a new methodology that fulfills those conditions, making it possible to carry out more complex analyses that require many simulations in a short time and at low computational costs. The new methodology to obtain the thermo-mechanical response to non-uniform heating and mechanical loads is general, simple, accurate, and avoids using complex and high-cost finite elements, simplifying the structural modeling, and reducing the computational analysis cost. As a result, complex structural fire engineering problems such as probabilistic and optimization analysis can be handled much more easily, representing a significant step toward the generalized application of performance-based approaches to deal with fire effects on structures. The procedure uses simple but advanced Timoshenko's beam-type finite elements and represents the non-uniform temperature space–time field through a mean value of the temperature and the two mean values of the section thermal gradients which are variable in time during the fire. The methodology is satisfactorily validated with results (experimental and numerical) of the Cardington frame test and captures 3D-phenomena such as buckling, flexural–torsional buckling, and warping.